Hydrodynamic Performances on Flexitank Package for Bulk Liquid Transportation Subjected to Ship Motion Using CFD - Mohammad Aizal Almazan Jamil; Nofrizalidris Darlis (Progress in Engineering Application and Technology, 2024)
Bulk liquid transportation can be used to transport various useful materials overseas via sea transportation. There are a lot of ways to transport liquid in bulk overseas and using flexitank is one of them. However, transporting useful liquids such as water, latex and crude palm oil (CPO) could cause a sloshing phenomenon to happen which potentially could cause flexitank to be damaged. This problem could be address by determining the critical parameter on ship motion for flexitank problem. Besides, with the usage for computational fluid dynamics (CFD) software such as Ansys Fluent, the boundary conditions such as fluid density, filling volume and roll angle of ship motion could be applied. In this case, the fluid density that was chosen is 997 kg/m3, 890 kg/m3 and 950 kg/m3 which are water, CPO and latex respectively. Moreover, the targeted fillingvolume of the flexitank was reference, +1%, +2%, and +3%. This means the chosen filling volume was 21,000 L, 21,210 L, 21, 420 L and 21,630 L respectively. Furthermore, by using CDF software such as Ansys Fluent, hydrodynamic performances such as pressure distribution, sloshing force and wall shear stress could be obtained. In addition, these hydrodynamic performances could be applied to determine the suitable filling volume for water, CPO and latex as filling fluid inside flexitank respectively. Thus, it is recommended to choose 2% as a suitable filling volume for water and CPO while 1% for latex